Pengaruh Penerapan Model Pembelajaran Berbasis Project Citizen Terhadap Kemampuan Berpikir Kritis Siswa Kelas VIII SMP NEGERI 16 Tebo Pada Mata Pelajaran PPKN - Pitri, Arnia; Anderson, Irzal (Citizenship Education, Faculty of Education, Jambi University, 2023)
This research was motivated by the low critical thinking ability of students in Civics subjects which only reached a percentage of 40%